2020
DOI: 10.1002/pssa.202000389
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Absorption Performance of FeSiCr Nanoparticles by Changing the Shape Anisotropy

Abstract: FeSiCr nanoparticles are prepared by plasma arc discharge and ball milling processes. After ball milling, the surface area and sizes of the FeSiCr nanoparticles become larger, and most of the nanoparticles become uneven. The increasing surface area and sizes of nanoparticles contribute to the electrical conductivity, enhance the space charge polarization between metal ions, and increase the shape anisotropy of FeSiCr nanoparticles. The inhomogeneity of nanoparticles reduces the activation energy (ΔE) of the Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Compared with dielectric and ferrite absorbers, ferromagnetic alloys possess better magnetic properties and more appropriate EM parameters, which are beneficial for their microwave absorption properties (MAP) [4,5]. The FeSiCr alloy powder is one such ferromagnetic MAM alloy with high permeability, high saturation magnification and high Curie temperature; in addition, the presence of Si and Cr improves its corrosion resistance and oxidation resistance [6,7]. Furthermore, through flake-shaped deformation induced by the ball milling process, the Snoek's limit of FeSiCr can be overcome to obtain higher permeability in the GHz band by improving planar anisotropy, inhibit the eddy current and skin effect of magnetic alloys and achieve a larger specific surface area that enhances dielectric loss (including conduction loss and polarization loss) in the absorbent [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with dielectric and ferrite absorbers, ferromagnetic alloys possess better magnetic properties and more appropriate EM parameters, which are beneficial for their microwave absorption properties (MAP) [4,5]. The FeSiCr alloy powder is one such ferromagnetic MAM alloy with high permeability, high saturation magnification and high Curie temperature; in addition, the presence of Si and Cr improves its corrosion resistance and oxidation resistance [6,7]. Furthermore, through flake-shaped deformation induced by the ball milling process, the Snoek's limit of FeSiCr can be overcome to obtain higher permeability in the GHz band by improving planar anisotropy, inhibit the eddy current and skin effect of magnetic alloys and achieve a larger specific surface area that enhances dielectric loss (including conduction loss and polarization loss) in the absorbent [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 , 4 , 5 , 6 , 7 ], dielectric loss type (ferroelectric ceramics, MnO 2 , etc. ), and magnetic loss type (ferrite [ 8 , 9 , 10 , 11 ], carbonyl iron [ 12 , 13 , 14 , 15 , 16 ], magnetic metal alloy powder [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], etc.). Magnetic alloy powders have been widely studied for their high absorption intensity and wide absorption band.…”
Section: Introductionmentioning
confidence: 99%
“…Duan et al [ 18 ] used a high-energy ball milling method to obtain FeCoNi powder with different ball milling times. They found that, with the increase in ball milling time, the wave absorption performance of the powder was enhanced, and the RL min reached −32.4 dB when the ball milling time was 90 h. Chen et al [ 19 ] and Duan et al [ 20 ] prepared FeSiCr and FeSiAl powders, respectively, and studied the effect of ball milling time on the wave absorption performance. The results showed that the absorbing properties of the alloy were enhanced after ball milling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FeSiCr alloy alloys (FSC) present better DC-bias superposition characteristics than NiCuZn ferrites [ 4 , 5 , 6 , 7 ] and are hence widely used in power molding coils [ 8 , 9 , 10 , 11 ]. Moreover, a Cr-rich oxidation layer formed on the FSC surface can increase electrical resistivity to reduce the eddy current loss and improve the oxidation and corrosion resistance of the inductors [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%